The dimensions of national competitiveness: The empirical analysis based on The World Economic Forum’s data - Adamkiewicz, Hanna G. (Economics and Business Review, 2019)
The aim of this research is to determine the minimum number of uncorrelated dimensions which can describe national competitiveness (NC). NC is thought of as the ability of a nation to provide a conducive environment for its firms to prosper. It is shown that the environment affects national productivity catalytically through the interactions with the production factors while itself remaining unchanged. Selected World Economic Forum’s indicators are used for determining the components of the environment. The Principal Component Analysis has revealed three orthogonal dimensions of NC. Countries are represented by the points in the three-dimensional space. The weighted Euclidean distance from the origin to the ith point is proposed as a novel measure of the ith country’s level of NC.